2019
DOI: 10.1097/ta.0000000000002396
|View full text |Cite
|
Sign up to set email alerts
|

Single-lateral cervical radiograph in pediatric trauma is equivalent to multiple views

Abstract: BACKGROUND Cervical spine injuries (CSI) are rare within the pediatric population. Due to the significant consequences of missed CSI, children are often imaged excessively. In an attempt to decrease imaging of the cervical spine in children, we reviewed abnormal cervical radiographs (XR) to determine if the diagnosis of CSI could be made using a single-lateral cervical radiograph (LAT). Furthermore, we reviewed cervical computed tomography (CT) and magnetic resonance imaging (MRI) to ensure there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several recent reports have demonstrated excellent sensitivity of X-ray for CSI [20, 21]. Lindholm et al [22] showed that even a single lateral-view X-ray was equivalent to multiple views and had 100% sensitivity for bony injuries. Another concern of MRI is that of “false positives,” where minor injuries on imaging may prompt maintenance of a cervical collar for prolonged periods while inpatient or on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated excellent sensitivity of X-ray for CSI [20, 21]. Lindholm et al [22] showed that even a single lateral-view X-ray was equivalent to multiple views and had 100% sensitivity for bony injuries. Another concern of MRI is that of “false positives,” where minor injuries on imaging may prompt maintenance of a cervical collar for prolonged periods while inpatient or on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients have been shown previously to have low rates of CSI. [5][6][7][8][9]13 Those without a diving/axial load mechanism, along with a normal mental status and intact neurologic examination, have even lower risk. 1,6 However, posterior cervical midline tenderness often prompts concern for CSI.…”
Section: Discussionmentioning
confidence: 99%
“…B lunt traumatic injury is the reason for many urgent pediatric visits to an emergency department (ED). [1][2][3][4] Although cervical spine injury (CSI) after blunt trauma is rare in the pediatric population, [5][6][7][8][9] the consequences of CSI can be devastating. Thus, timely and accurate cervical spine assessment is critical.…”
mentioning
confidence: 99%
See 2 more Smart Citations